Central Bank–Driven Mispricing - Pelizzon, Loriana; Subrahmanyam, Marti G.; Tomio, Davide (Journal of Financial Economics, 2025)
We explore whether Quantitative Easing (QE) negatively affected the functioning of the treasury market. Focusing on the arbitrage between European sovereign bonds and their futures contracts, we show that the scarcity of treasuries created by QE led to a disconnect between the prices of identical assets. We identify three channels: reduced bond market liquidity, increased funding costs in the repo market, and a higher cost of carry. A change in a policy instrument allows us to identify scarcity as the main driver and rule out alternatives, such as balance sheet costs. Our results extend to other arbitrage relations involving treasuries.